Polyvinyl alcohol film for polarizing film production, method for producing same, and polarizing
By controlling the half-value width of the molecular weight differential distribution curve of the polyvinyl alcohol-based film and the dissolution test conditions in the boric acid solution, the problem of large dissolution amount of polyvinyl alcohol-based resin in the polarizing film manufacturing was solved, and a low-pollution and high-efficiency polarizing film production was achieved.
Patent Information
- Application Number
- CN202380065464.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-26
- Filing Date
- 2023-12-25
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, it is difficult to effectively suppress the dissolution amount of polyvinyl alcohol-based resin in the pharmaceutical liquid containing boric acid during the polarizing film manufacturing process, resulting in contamination of the pharmaceutical liquid tank and degradation of the optical performance of the polarizing film.
By controlling the half-value width of the corresponding polyvinyl alcohol peak of the molecular weight differential distribution curve of the gel permeation chromatography within a specific range, the dissolution amount of the polyvinyl alcohol-based resin is reduced in combination with the specific boric acid solution.
It effectively suppresses the pollution of the medicine liquid tank during the polarizing film manufacturing process, improves productivity, and reduces foreign object defects in the polarizing film, achieving high-quality polarizing film production.
Smart Images

Figure BDA0005307723660000251
Abstract
Description
Technical Field
[0001] The present invention relates to a polyvinyl alcohol-based film for use in the manufacture of polarizing films, and more particularly, to a polyvinyl alcohol-based film for use in the manufacture of polarizing films, which has less elution of impurities in an aqueous boric acid solution used in a cross-linking and stretching process during the manufacture of polarizing films, thereby suppressing contamination of a chemical solution tank during the manufacture of polarizing plates and enabling the production of polarizing films with good productivity. Background Art
[0002] In recent years, liquid crystal display devices have developed significantly and are widely used in smartphones, tablet computers, personal computers, LCD TVs, projectors, car panels, etc.
[0003] The liquid crystal display device uses a polarizing film, and as the polarizing film, a film made by adsorbing and orienting iodine on a polyvinyl alcohol film is mainly used. In recent years, with the high-definition, high-brightness, large-scale, and thin-type screens, there is a need for a polarizing film with better polarization performance than previous products, no color unevenness, and wide and long strips.
[0004] Usually, the polarizing film is made by rolling the polyvinyl alcohol film of the blank from a roll, conveying it along the length direction (MD direction), and swelling it with water (including warm water), and then dyeing it with iodine, stretching it for iodine orientation, and crosslinking it with boric acid for fixing the orientation state. The undesirable conditions generated in these processes greatly reduce the productivity of the polarizing film. For example, in the swelling process, if impurities are dissolved from the polyvinyl alcohol film and contaminate the swelling tank, the contamination will spread in all subsequent processes. In addition, even if the contamination of the swelling process can be suppressed, if impurities are still dissolved from the polyvinyl alcohol film in the subsequent dyeing process, boric acid crosslinking process, etc., the optical properties of the obtained polarizing film will not only decrease, but also the filtration and exchange of the liquid used in each process will require a lot of labor and cost, and the productivity will be greatly reduced. As the impurities, low molecular weight polyvinyl alcohol resins (including oligomers) present in the polyvinyl alcohol film can be listed.
[0005] In particular, low molecular weight polyvinyl alcohol resin dissolved in a solution containing boric acid will form an association with iodine and boric acid in the solution and become a foreign matter (precipitate) containing polyvinyl alcohol resin. If the foreign matter floats in the solution and adheres to the surface of the polarizing film being processed, it will become a foreign matter defect of the polarizing film finally obtained, so it needs to be removed.
[0006] On the other hand, the polyvinyl alcohol film of the blank is usually prepared by dissolving the polyvinyl alcohol resin as a raw material in water, and the aqueous solution (film-making stock solution) is manufactured by continuous casting. Specifically, the aqueous solution of the polyvinyl alcohol resin is ejected and cast onto a casting mold such as a casting drum or an endless belt to make a film, and the obtained film is peeled off from the casting mold, while being transported along the length direction (MD direction), while being manufactured by drying and heat treatment. Among these processes, the drying process is an important process for controlling the eluted components from the polyvinyl alcohol film. If the drying method in the drying process is inappropriate, there is a tendency for the polyvinyl alcohol resin eluted during the manufacture of the polarizing film to increase.
[0007] As methods for improving the above-mentioned problems, for example, a polyvinyl alcohol film having a reduced amount of polyvinyl alcohol resin eluted into water (see Patent Document 1) and a method for removing foreign matter (precipitate) containing polyvinyl alcohol resin generated in a chemical solution tank (see Patent Document 2) have been proposed.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2009-221462
[0011] Patent Document 2: Japanese Patent Application Publication No. 2021-047397 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] However, in the disclosed technology of Patent Document 1, the concentration of the polyvinyl alcohol resin eluted after immersing a 10 cm square film in 1 liter of water at 50°C for 4 hours is 10 to 50 ppm. 2 Then there are 1000~5000ppm / m 2 The polyvinyl alcohol-based resin is eluted, and since polarizing films are manufactured with high production efficiency according to the needs of polarizing films in recent years, it is necessary to further reduce the resin elution amount. In addition, the dissolution inhibition in the liquid containing boric acid is not disclosed, and further improvement is required.
[0014] On the other hand, in the disclosed technology of the above-mentioned Patent Document 2, by using a bubbling device, foreign matter (precipitate) containing polyvinyl alcohol resin produced in the solution tank can be efficiently removed, thereby enabling long-term continuous operation and improving production efficiency. However, in order to obtain further effects, it is necessary to suppress the dissolution of polyvinyl alcohol resin from the polyvinyl alcohol film in the treatment solution containing boric acid.
[0015] Therefore, in this context, the present invention provides a polyvinyl alcohol film for polarizing film manufacturing, which has a small amount of polyvinyl alcohol resin eluted in a boric acid-containing solution during polarizing film manufacturing, and suppresses contamination of the solution tank during polarizing film manufacturing, thereby enabling a polarizing film with few foreign matter defects to be obtained with good productivity.
[0016] Solutions for solving problems
[0017] However, the present inventors focused on the relationship between the molecular weight differential distribution curve in gel permeation chromatography and the dissolution amount of polyvinyl alcohol resin in the boric acid solution of the polyvinyl alcohol film, and found that when the half-value width of the peak corresponding to polyvinyl alcohol in the molecular weight differential distribution curve of gel permeation chromatography is within a specific range, the above-mentioned problem is solved, the contamination of the chemical solution in the polarizing film manufacturing process is suppressed, and the polarizing film with less foreign matter defects can be manufactured with good productivity.
[0018] That is, the present invention has the following aspects. [1]
[0020] A polyvinyl alcohol-based film for polarizing film production, characterized in that the half-value width of the peak corresponding to polyvinyl alcohol in the molecular weight differential distribution curve of gel permeation chromatography is less than 0.9, and the dissolution amount in the dissolution test in a boric acid solution conducted under the following condition (A) is 120 ppm / m 2 the following.
[0021] <Condition(A)>
[0022] (i) Five polyvinyl alcohol films with a width of 50 mm were prepared, and one of the films was mounted on a chuck stretching machine with a chuck distance of 40 mm.
[0023] (ii) The film was stretched to 2 times while being immersed in a water bath at 30°C for 2 minutes.
[0024] (iii) The film was stretched to 3 times while being immersed in an iodine / potassium iodide aqueous solution at 30° C. for 20 seconds.
[0025] (iv) Immerse in 100 mL of a 60° C. boric acid / potassium iodide aqueous solution for 5 minutes.
[0026] (v) The steps (i) to (iv) are repeated for the remaining four films in the same aqueous solution used in each step, and the solution of (iv) obtained after repeating the steps for five films is used as the eluent.
[0027] (vi) 20 mL of the eluate was mixed with 20 mL of a color developing reagent containing boric acid / iodine / potassium iodide, and the mixture was allowed to stand at 20° C. to prepare a sample solution.
[0028] (vii) For the sample solution, a UV-vis spectrum was obtained using a quartz cell with an optical path length of 100 mm, and the absorbance at 690 nm was read.
[0029] (viii) The concentration of the polyvinyl alcohol resin in the elution solution was calculated using a calibration curve of polyvinyl alcohol resin concentration versus absorbance at 690 nm prepared using solutions of known polyvinyl alcohol resin concentrations, and corrected using the area of the polyvinyl alcohol film used for elution. [2]
[0031] The polyvinyl alcohol-based film for producing a polarizing film according to [1], wherein the film has a thickness of 10 to 50 μm. [3]
[0033] The polyvinyl alcohol-based film for producing a polarizing film according to [1] or [2], wherein the weight swelling degree is 185 to 200%. [4]
[0035] A method for producing a polyvinyl alcohol-based film for polarizing film production as described in any one of [1] to [3], characterized in that it comprises: a film-forming step of continuously ejecting and casting an aqueous solution of a polyvinyl alcohol-based resin onto a casting die or a belt to form a film to obtain a film, a drying step of drying the film obtained by the film-forming at a temperature above 105°C, and a heat treatment step of heat-treating the dried film. [5]
[0037] A polarizing film characterized by being obtained by using the polyvinyl alcohol-based film for producing a polarizing film according to any one of [1] to [3].
[0038] Effects of the Invention
[0039] The polyvinyl alcohol film for polarizing film manufacturing of the present invention has a small amount of polyvinyl alcohol resin eluted in a boric acid-containing solution during polarizing film manufacturing, thereby suppressing contamination of the solution tank during polarizing film manufacturing. Therefore, it is useful as a raw film for manufacturing polarizing films with few foreign matter defects at high productivity. DETAILED DESCRIPTION
[0040] Hereinafter, although the form for implementing this invention is demonstrated in detail, this invention is not limited to these.
[0041] In the present invention, when “X to Y” (X and Y are arbitrary numbers) is expressed, it means “X or more and Y or less” unless otherwise specified, and also includes “preferably greater than X” or “preferably less than Y”.
[0042] When expressed as "X or more" (X is an arbitrary number) or "Y or less" (Y is an arbitrary number), it also includes the meaning of "preferably greater than X" or "preferably less than Y".
[0043] The term "film" in the present invention also includes "tape" and "sheet".
[0044] The term "main component" as used herein means a component that has a significant influence on the properties of its object, and the content of the component is usually 50% by mass or more, preferably 55% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and may also be 100% by mass.
[0045] The polyvinyl alcohol-based film for polarizing film production according to one embodiment of the present invention (hereinafter sometimes referred to as "the polyvinyl alcohol-based film of the present invention") is characterized in that the half-value width of the peak corresponding to polyvinyl alcohol in the molecular weight differential distribution curve of gel permeation chromatography is less than 0.9, and the dissolution amount in the dissolution test in a boric acid solution conducted under the following condition (A) is 120 ppm / m 2 the following.
[0046] The half value width of the peak corresponding to polyvinyl alcohol in the molecular weight differential distribution curve of the polyvinyl alcohol-based film of the present invention by gel permeation chromatography must be 0.9 or less, preferably 0.8 or less, and particularly preferably 0.75 or less.
[0047] The lower limit of the half-value width is usually 0.3 or more, and preferably 0.5 or more.
[0048] When the half-value width is 0.9 or less, the amount of polyvinyl alcohol-based resin dissolved in the liquid containing boric acid during the manufacture of the polarizing film is small, and the liquid contamination during the manufacture of the polarizing film can be suppressed, thereby obtaining a polyvinyl alcohol-based film with few foreign matter defects and excellent productivity. In other words, if the half-value width is higher than the above upper limit, the polyvinyl alcohol-based resin dissolves in a large amount in the liquid containing boric acid during the manufacture of the polarizing film and contaminates the liquid, and forms an association with the boric acid and iodide ions in the liquid to generate foreign matter defects, thereby failing to achieve the effect of the present invention.
[0049] Here, the molecular weight differential distribution curve in the present invention is a molecular weight differential distribution curve obtained by gel permeation chromatography measurement using polyethylene oxide and polyethylene glycol as standard samples, wherein the horizontal axis is the common logarithm of the molecular weight M logM, and the vertical axis is dw / dlogM, which is the derivative of the concentration fraction w using the common logarithm of the molecular weight M logM.
[0050] The half-value width refers to the width (full width at half maximum) of logM which is half the maximum value of dw / dlogM in the molecular weight differential distribution curve.
[0051] It should be noted that the molecular weight M here refers to the molecular weight converted to a standard sample.
[0052] Furthermore, the gel permeation chromatography measurement of the polyvinyl alcohol resin of the polyvinyl alcohol film for polarizing film production may be performed directly by dissolving the film in a mobile phase, or may be performed after removing components other than the polyvinyl alcohol resin by extraction or the like as a pretreatment.
[0053] Furthermore, the polyvinyl alcohol film of the present invention must have a dissolution amount of 120 ppm / m in a boric acid solution dissolution test conducted under the following condition (A). 2 Below, preferably 100ppm / m 2 Below, particularly preferably 80ppm / m 2 Below, more preferably 60ppm / m 2 Below. In addition, the lower limit is usually 10ppm / m 2 Above, preferably 20ppm / m 2 above.
[0054] The dissolution amount in the dissolution test in the boric acid solution conducted using the following condition (A) is below the above-mentioned upper limit value, the dissolution amount of the polyvinyl alcohol resin in the boric acid-containing solution during the manufacture of the polarizing film is small, and the contamination of the solution during the manufacture of the polarizing film can be suppressed, thereby achieving a polyvinyl alcohol film with fewer foreign matter defects and excellent productivity.
[0055] In other words, if the dissolution amount in the dissolution test in the boric acid solution conducted using the following condition (A) exceeds the above-mentioned upper limit value, the polyvinyl alcohol-based resin will dissolve in large quantities in the boric acid-containing solution during the manufacture of the polarizing film, contaminating the solution and forming an association with the boric acid and iodide ions in the solution to produce foreign matter defects, thereby failing to achieve the effect of the present invention.
[0056] <Condition(A)>
[0057] (i) Five polyvinyl alcohol films with a width of 50 mm were prepared, and one of the films was mounted on a chuck stretching machine with a chuck distance of 40 mm.
[0058] (ii) The film was stretched to 2 times while being immersed in a water bath at 30°C for 2 minutes.
[0059] (iii) The film was stretched to 3 times while being immersed in an iodine / potassium iodide aqueous solution at 30° C. for 20 seconds.
[0060] (iv) Immerse in 100 mL of a 60° C. boric acid / potassium iodide aqueous solution for 5 minutes.
[0061] (v) The steps (i) to (iv) are repeated for the remaining four films in the same aqueous solution used in each step, and the solution of (iv) obtained after repeating the steps for five films is used as the eluent.
[0062] (vi) 20 mL of the eluate obtained above and 20 mL of a color developing reagent containing boric acid / iodine / potassium iodide were mixed and allowed to stand at 20° C. to prepare a sample solution.
[0063] (vii) For the sample solution, a UV-vis spectrum was obtained using a quartz cell with an optical path length of 100 mm, and the absorbance at 690 nm was read.
[0064] (viii) The concentration of the polyvinyl alcohol resin in the elution solution was calculated using a calibration curve of polyvinyl alcohol resin concentration versus absorbance at 690 nm prepared using solutions of known polyvinyl alcohol resin concentrations, and corrected using the area of the polyvinyl alcohol film used for elution.
[0065] As a method for controlling the half-value width of the peak corresponding to polyvinyl alcohol in the molecular weight differential distribution curve of the gel permeation chromatography of the above-mentioned polyvinyl alcohol film within a specific range, for example, there can be listed: a method of removing low-molecular-weight components by washing the polyvinyl alcohol resin with a solvent utilizing the difference in solubility between low-molecular-weight components and high-molecular-weight components, a method of reducing the deviation of the molecular weight of the polyvinyl alcohol resin obtained by controlling free radical polymerization, etc. In the present embodiment, a method by controlling free radical polymerization is preferred, and from the viewpoint of easy control of the half-value width, a method using an organic cobalt complex as a controlling agent is particularly preferred.
[0066] Hereinafter, the method for producing the polyvinyl alcohol film of the present invention will be described in more detail in the order of the steps, but the polyvinyl alcohol film of the present invention is not limited to these embodiments.
[0067] The polyvinyl alcohol film of the present invention is preferably produced through the following steps (A) to (C), and preferably also through the step (D) as necessary.
[0068] Step (A): a step of preparing a polyvinyl alcohol-based resin aqueous solution.
[0069] Step (B): a step of casting an aqueous solution of a polyvinyl alcohol-based resin on a casting die to form a film.
[0070] Step (C): a step of drying the formed thin film.
[0071] Step (D): a step of heat-treating the obtained thin film.
[0072] <Step (A)>
[0073] The step (A) is a step of preparing an aqueous solution of a polyvinyl alcohol-based resin (liquid preparation step).
[0074] First, the polyvinyl alcohol-based resin and the polyvinyl alcohol-based resin aqueous solution which are materials of the polyvinyl alcohol-based film will be described.
[0075] In the present embodiment, as the polyvinyl alcohol resin constituting the polyvinyl alcohol film, an unmodified polyvinyl alcohol resin, that is, a resin produced by saponifying polyvinyl acetate obtained by polymerizing vinyl acetate, is generally used. As required, a resin obtained by saponifying a copolymer of vinyl acetate and a small amount (generally less than 10 mol %, preferably less than 5 mol %) of a component that can copolymerize with vinyl acetate can also be used. As a component that can copolymerize with vinyl acetate, for example, unsaturated carboxylic acids (for example, including salts, esters, amides, nitriles, etc.), olefins with 2 to 30 carbon atoms (for example, ethylene, propylene, n-butene, isobutylene, etc.), vinyl ethers, unsaturated sulfonates, etc. can be listed. In addition, a modified polyvinyl alcohol resin obtained by chemically modifying the hydroxyl group after saponification can also be used. These can be used alone or in combination of two or more.
[0076] In addition, as the polyvinyl alcohol-based resin, a polyvinyl alcohol-based resin having a 1,2-diol structure in the side chain can also be used. The polyvinyl alcohol-based resin having a 1,2-diol structure in the side chain can be obtained, for example, by the following methods: (i) a method of saponifying a copolymer of vinyl acetate and 3,4-diacetoxy-1-butene, (ii) a method of saponifying and decarbonating a copolymer of vinyl acetate and vinyl ethylene carbonate, (iii) a method of saponifying and deketalizing a copolymer of vinyl acetate and 2,2-dialkyl-4-vinyl-1,3-dioxolane, (iv) a method of saponifying a copolymer of vinyl acetate and glycerol monoallyl ether, etc.
[0077] The weight average molecular weight of the polyvinyl alcohol resin is preferably 60,000 to 150,000, particularly preferably 70,000 to 130,000, and further preferably 70,000 to 120,000. If the weight average molecular weight is too small, it is difficult to obtain sufficient optical properties when the polyvinyl alcohol resin is used as an optical film, and if it is too large, it is difficult to stretch the polyvinyl alcohol film when the polarizing film is manufactured. It should be noted that the weight average molecular weight of the polyvinyl alcohol resin is the weight average molecular weight measured by the GPC method.
[0078] The dispersion degree (weight average molecular weight / number average molecular weight) of the polyvinyl alcohol-based resin is preferably 1.95 to 2.20, particularly preferably 1.96 to 2.15, and further preferably 1.97 to 2.10.
[0079] If the dispersion degree is too small, stretching tends to be difficult when the polyvinyl alcohol-based film is used to produce a polarizing film, while if it is too large, sufficient optical performance tends to be difficult to obtain when the polyvinyl alcohol-based resin is used as an optical film.
[0080] In addition, the weight average molecular weight and number average molecular weight when measuring the dispersion degree of the above-mentioned polyvinyl alcohol-based resin are the weight average molecular weight and number average molecular weight measured by the GPC method.
[0081] The average saponification degree of the polyvinyl alcohol resin is usually preferably 98 mol% or more, particularly preferably 99 mol% or more, further preferably 99.5 mol% or more, and particularly preferably 99.8 mol% or more. If the average saponification degree is too low, there is a tendency that sufficient optical performance cannot be obtained when the polyvinyl alcohol film is used as a polarizing film.
[0082] Here, the average saponification degree in the present invention is measured based on JIS K 6726.
[0083] As the polyvinyl alcohol-based resin, two or more types different in modification type, modification amount, weight average molecular weight, average saponification degree, etc. may be used in combination.
[0084] In order to set the half width of the molecular weight distribution and the molecular weight differential distribution curve to the desired values, the polyvinyl alcohol-based resin is preferably obtained by adding a control agent during the polymerization of vinyl acetate to control the free radical polymerization. The control agent added during the polymerization is not particularly limited, but from the viewpoint of controllability, a method using an organic cobalt complex as the control agent is preferred.
[0085] The polyvinyl alcohol resin aqueous solution may contain, in addition to the polyvinyl alcohol resin, a commonly used plasticizer such as glycerol, diglycerol, triglycerol, ethylene glycol, triethylene glycol, polyethylene glycol, trimethylolpropane, and at least one surfactant of nonionic, anionic, and cationic properties as required, which is more preferred from the viewpoint of film forming properties. These may be used alone or in combination of two or more.
[0086] The composition concentration of the polyvinyl alcohol-based resin aqueous solution obtained in this way is preferably 15 to 60% by mass, particularly preferably 17 to 55% by mass, and further preferably 20 to 50% by mass. If the composition concentration of the aqueous solution is too low, the drying load increases and the production capacity tends to decrease, while if it is too high, the viscosity tends to become too high and it tends to become difficult to dissolve uniformly.
[0087] Then, the obtained polyvinyl alcohol-based resin aqueous solution is subjected to deaeration. As deaeration methods, methods such as static deaeration and deaeration based on a multi-screw extruder can be listed. As a multi-screw extruder, as long as it is a multi-screw extruder with a discharge port, a twin-screw extruder with a discharge port is usually used.
[0088] <Process (B)>
[0089] The step (B) is a step of casting an aqueous solution of a polyvinyl alcohol-based resin on a casting die to form a film (film forming step).
[0090] After the degassing treatment, a fixed amount of the polyvinyl alcohol-based resin aqueous solution is introduced into a T-slit die, and ejected and cast onto a rotating casting drum to form a film by a continuous casting method.
[0091] The resin temperature of the polyvinyl alcohol-based resin aqueous solution at the outlet of the T-slit die is preferably 80 to 100°C, particularly preferably 85 to 98°C.
[0092] If the resin temperature of the polyvinyl alcohol-based resin aqueous solution is too low, the fluidity tends to be poor, and if it is too high, the solution tends to foam.
[0093] The viscosity of the polyvinyl alcohol-based resin aqueous solution when discharged is preferably 50 to 200 Pa·s, particularly preferably 70 to 150 Pa·s.
[0094] If the viscosity of the aqueous solution is too high, the fluidity tends to be poor, and if it is too low, film casting tends to become difficult.
[0095] The discharge speed of the polyvinyl alcohol-based resin aqueous solution discharged from the T-slit die to the casting drum is preferably 0.2 to 5 m / min, particularly preferably 0.4 to 4 m / min, and further preferably 0.6 to 3 m / min.
[0096] If the ejection speed is too slow, productivity tends to decrease, and if it is too fast, casting tends to become difficult.
[0097] The diameter of the casting drum is preferably 2 to 5 m, particularly preferably 2.4 to 4.5 m, and further preferably 2.8 to 4 m.
[0098] If the diameter is too small, the drying zone on the casting drum becomes short, so that the speed tends to be difficult to increase, while if it is too large, the conveying performance tends to decrease.
[0099] The width of the casting drum is preferably 4 m or more, particularly preferably 4.5 m or more, further preferably 5 m or more, and particularly preferably 5 to 8 m.
[0100] If the width of the casting drum is too small, productivity tends to decrease.
[0101] The rotation speed of the casting drum is preferably 3 to 50 m / min, particularly preferably 7 to 40 m / min, and further preferably 10 to 35 m / min.
[0102] If the rotation speed is too slow, productivity tends to decrease, and if it is too fast, drying tends to be insufficient.
[0103] The upper limit of the surface temperature of the casting drum is preferably 100° C. or lower, particularly preferably 97° C. or lower, further preferably 95° C. or lower, and particularly preferably 92° C. or lower, from the viewpoint of suppressing foaming during drying and obtaining a film with excellent appearance. In addition, from the viewpoint of excellent releasability when the film is peeled off from the casting die, the lower limit is preferably 60° C. or higher, particularly preferably 65° C. or higher, further preferably 70° C. or higher, particularly preferably 75° C. or higher, and particularly preferably 80° C. or higher.
[0104] <Process (C)>
[0105] Step (C) is a step of drying the film formed as described above (drying step).
[0106] In the present embodiment, the method for drying the film in the drying step is not particularly limited, and the film may be dried using a method of drying with a hot roll, a method of drying in a drying furnace, or the like.
[0107] When drying is performed with hot rollers in the drying step, the film peeled off from the casting drum (the film after film formation) is conveyed in the flow direction (MD direction) using a nip roller or the like, and the surface and back of the film are alternately contacted with a plurality of hot rollers to perform drying. The hot rollers are, for example, rollers with a diameter of 0.2 to 2 m, the surface of which is subjected to hard chrome plating or mirror finishing, and 2 to 30 rollers are usually used for drying, preferably 10 to 25 rollers are used for drying.
[0108] The drying temperature in the drying process refers to the surface temperature of the hot roller when drying is performed with a hot roller, and refers to the temperature in the drying furnace when drying is performed in a drying furnace. The lower limit of the drying temperature in the drying process is usually 60° C. or higher, preferably 70° C. or higher, particularly preferably 85° C. or higher, further preferably 100° C. or higher, and most preferably 105° C. or higher.
[0109] The upper limit of the drying temperature is usually 150° C. or lower, preferably 140° C. or lower, particularly preferably 135° C. or lower, further preferably 130° C. or lower, and most preferably 125° C. or lower.
[0110] If the drying temperature is too low, drying tends to be poor, while if it is too high, excessive drying tends to cause poor appearance such as waviness.
[0111] For the drying time, the upper limit is preferably 30 minutes or less, particularly preferably 20 minutes or less, further preferably 15 minutes or less, and particularly preferably 10 minutes or less. In addition, the lower limit is preferably 20 seconds or more, particularly preferably 25 seconds or more, further preferably 27 seconds or more, and particularly preferably 30 seconds or more.
[0112] If the drying time is too long, dyeability during production of the polarizing film tends to decrease, and if it is too short, drying tends to be poor.
[0113] Among them, for the drying time when drying in a drying furnace, the upper limit is preferably 30 minutes or less, particularly preferably 20 minutes or less, further preferably 15 minutes or less, and particularly preferably 10 minutes or less. In addition, the lower limit is preferably 30 seconds or more, particularly preferably 1 minute or more, further preferably 3 minutes or more, and particularly preferably 5 minutes or more.
[0114] For the drying time when drying with a hot roller, the upper limit is preferably below 60 seconds, particularly preferably below 55 seconds, further preferably below 50 seconds, and particularly preferably below 45 seconds. In addition, the lower limit is preferably above 20 seconds, particularly preferably above 25 seconds, further preferably above 27 seconds, and particularly preferably above 30 seconds.
[0115] If the hot roll drying time is too long, the dyeability during the production of the polarizing film tends to be reduced. If it is too fast, the film tends to be wrinkled or bent during the swelling step during the production of the polarizing film, and the appearance of the polarizing film tends to be reduced.
[0116] <Process (D)>
[0117] Step (D) is a step of heat-treating the obtained thin film (heat-treating step).
[0118] The film that has been subjected to the step (C) may be heat-treated using, for example, a drying furnace, a floating dryer, or the like.
[0119] The temperature of the heat treatment, for example, refers to the temperature in the drying furnace when the heat treatment is performed in a drying furnace, and refers to the temperature in the floating dryer when the heat treatment is performed using a floating dryer. The upper limit of the heat treatment temperature is preferably 140°C or less, particularly preferably 135°C or less, further preferably 130°C or less, and particularly preferably 125°C or less. In addition, the lower limit is preferably 60°C or more, particularly preferably 75°C or more, further preferably 105°C or more, and particularly preferably 110°C or more.
[0120] If the heat treatment temperature is too high, the dyeability during the production of the polarizing film tends to decrease, while if it is too low, the film tends to wrinkle or bend during the swelling step during the production of the polarizing film, and the appearance of the polarizing film tends to decrease.
[0121] Furthermore, the heat treatment time is preferably 20 to 100 seconds, particularly preferably 40 to 70 seconds.
[0122] It should be noted that the heating in the drying step and the heating in the heat treatment step are that the former is heating to volatilize the water from the film, whereas the latter is further heating the film to adjust the crystal structure in the film.
[0123] [Polyvinyl alcohol film]
[0124] In this way, a polyvinyl alcohol-based film is obtained through the above steps (A) to (D), and is finally wound into a roll to become a product.
[0125] From the viewpoint of the production stability of the polarizing film, the lower limit of the thickness of the polyvinyl alcohol film of the present invention is preferably 10 μm or more, particularly preferably 15 μm or more, further preferably 20 μm or more, and particularly preferably 25 μm or more. In addition, from the viewpoint of reducing the warpage of a liquid crystal display using a polarizing film made of a polyvinyl alcohol film, the upper limit is preferably 70 μm or less, particularly preferably 50 μm or less, and further preferably 40 μm or less.
[0126] The length of the polyvinyl alcohol-based film of the present invention is preferably 4 km or longer from the viewpoint of increasing the area of the polarizing film, and is particularly preferably 5 to 50 km from the viewpoint of transport quality.
[0127] The width of the polyvinyl alcohol film of the present invention is preferably 1 m or more, more preferably 2 m or more, particularly preferably 3 m or more, and further preferably 3.5 m or more. In addition, from the viewpoint of widening the width of the polarizing film, it is preferably 4 m or more, particularly preferably 5 m or more, and from the viewpoint of avoiding breakage during the manufacture of the polarizing film, it is further preferably 5 to 6 m.
[0128] The weight swelling degree of the polyvinyl alcohol film of the present invention is preferably 185 to 200%. The lower limit is particularly preferably 186% or more, more preferably 187% or more, and the upper limit is particularly preferably 199% or less, more preferably 198% or less.
[0129] If the weight swelling degree is lower than the above range, the stretchability during the production of the polarizing film tends to decrease, while if it exceeds the above range, the stretchability becomes good but the polarizing performance of the polarizing film tends to decrease.
[0130] The elastic modulus of the polyvinyl alcohol film of the present invention is preferably 250 N / mm 2 Above, particularly preferably 290N / mm 2 More than 400 N / mm 2As the upper limit, it is preferably 800 N / mm 2 Below, particularly preferably 700 N / mm 2 Below, more preferably 600N / mm 2 the following.
[0131] If the elastic modulus is too low, the thin polarizing film tends to be easily broken during production, while if it is too high, the stretchability during production of the polarizing film tends to decrease.
[0132] The amount of polyvinyl alcohol resin dissolved in water (ppm / m 2 ) is preferably 900ppm / m 2 Below, particularly preferably 800ppm / m 2 Below, more preferably 700ppm / m 2 Below, especially preferably 650ppm / m 2 Below. The lower limit is usually 0ppm / m 2 Above, preferably 50ppm / m 2 Above, particularly preferably 100 ppm / m 2 above.
[0133] When the elution amount in water is within the above range, the elution amount of the polyvinyl alcohol resin in water during polarizing film production is small, and liquid contamination during polarizing film production can be suppressed, thereby achieving a polyvinyl alcohol film with few foreign matter defects and excellent productivity.
[0134] The amount eluted into water can be measured, for example, by the method described in Examples below.
[0135] The polyvinyl alcohol-based film obtained by the production method according to one embodiment of the present invention is useful for optical applications and is particularly useful as a raw film for a polarizing film. Hereinafter, a method for producing a polarizing film and a polarizing plate including the polyvinyl alcohol-based film will be described.
[0136] [Method for producing polarizing film]
[0137] The polarizing film of one embodiment of the present invention is produced by extending the polyvinyl alcohol-based film obtained by the production method of this embodiment from a roll and conveying it in a horizontal direction, and then undergoing steps such as swelling, dyeing, boric acid crosslinking, stretching, washing, and drying.
[0138] The swelling process is carried out before the dyeing process, for example, by immersing the film in a swelling solution (swelling bath). The swelling process can be used to clean dirt on the surface of the polyvinyl alcohol film. In addition, swelling the polyvinyl alcohol film also has the effect of preventing uneven dyeing. In the swelling process, water is usually used as the swelling solution. If the main component of the swelling solution is water, additives such as iodide and surfactants, alcohol, etc. can also be added. The temperature of the swelling bath is usually around 10 to 45°C, and the immersion time in the swelling bath is usually about 0.1 to 10 minutes.
[0139] The dyeing process is carried out by bringing a liquid (dyeing solution) containing iodine or a dichroic dye into contact with the film, for example, by immersing it in the dyeing solution. The dyeing solution generally uses an aqueous solution of iodine-potassium iodide, and it is appropriate that the concentration of iodine is 0.1 to 2 g / L and the concentration of potassium iodide is 1 to 100 g / L. The dyeing solution may also contain a small amount of an organic solvent compatible with water other than the aqueous solvent. It is practical to have a dyeing time of about 30 to 500 seconds. The dyeing temperature is preferably 5 to 50°C.
[0140] The boric acid crosslinking process is carried out using a boron compound such as boric acid or borax. The boron compound is used in the form of an aqueous solution or a water-organic solvent mixed solution with a concentration of about 10 to 100 g / L. From the perspective of stabilizing the polarization performance, potassium iodide is preferably coexisted in the solution. The temperature during the treatment is about 30 to 70° C., and the treatment time is preferably about 0.1 to 20 minutes. In addition, a stretching operation can also be performed during the treatment as needed.
[0141] The stretching process preferably stretches the film 3 to 10 times along the uniaxial direction, and particularly preferably 3.5 to 7 times. At this time, it is okay to stretch it slightly in the right angle direction along the stretching direction (to prevent shrinkage in the width direction, or stretching above this). The temperature during stretching is preferably 40 to 170°C. Furthermore, as long as the stretching ratio is finally set to the aforementioned range, the stretching operation can be not only one stage, but also multiple times in the manufacturing process.
[0142] The cleaning process is carried out, for example, by immersing the film in an aqueous iodide solution such as water or potassium iodide, so that the precipitate produced on the surface of the film can be removed. When using an aqueous potassium iodide solution, the potassium iodide concentration is preferably about 10 to 1000 g / L. The temperature during the cleaning treatment is usually 5 to 50° C., preferably 10 to 45° C. The treatment time is usually 1 to 300 seconds, preferably 10 to 240 seconds. It should be noted that water cleaning and cleaning with an aqueous potassium iodide solution can also be appropriately combined.
[0143] The drying step is performed, for example, by drying at 40 to 100° C. for 0.1 to 10 minutes using a dryer.
[0144] The polarizing film thus obtained preferably has a degree of polarization of 99.90% or more, and more preferably 99.99% or more. If the degree of polarization is too low, the contrast in a liquid crystal display tends to decrease.
[0145] The degree of polarization is generally determined by the transmittance (H) measured at a wavelength λ when two polarizing films are stacked so that their orientation directions are in the same direction. 11 ), and the light transmittance (H) measured at a wavelength of λ when two polarizing films are overlapped so that their orientation directions are orthogonal to each other. 1 ), calculated according to the following formula (1).
[0146] Polarization degree=[(H 11 -H 1 ) / (H 11 +H 1 )] 1 / 2 …(1)
[0147] Furthermore, the single-unit transmittance of the polarizing film of the present embodiment is preferably 43% or more. If the single-unit transmittance is too low, it tends to be impossible to achieve high brightness of a liquid crystal display.
[0148] The single-body transmittance is a value obtained by measuring the light transmittance of the polarizing film alone using a spectrophotometer.
[0149] Next, a method for producing a polarizing plate using the polarizing film of the present embodiment will be described.
[0150] The polarizing film of this embodiment is suitable for manufacturing a polarizing plate having less color unevenness and excellent polarization performance.
[0151] [Polarizing Plate Manufacturing Method]
[0152] The polarizing plate is produced by bonding an optically isotropic resin film as a protective film to one or both sides of the polarizing film of the present embodiment with an adhesive. Examples of the protective film include films formed of acetylcellulose resins such as triacetylcellulose and diacetylcellulose, films formed of polyester resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polycarbonate resin films, cycloolefin resin films, acrylic resin films, and films formed of chain olefin resins such as polypropylene resins.
[0153] The lamination can be performed by a known method, for example, by uniformly applying a liquid adhesive composition to the polarizing film, the protective film, or both, laminating and pressing the two, and heating or irradiating with active energy rays.
[0154] It should be noted that, for example, a curable resin such as a urethane resin, an acrylic resin, or a urea resin may be coated on one or both sides of the polarizing film and cured to form a cured layer, thereby manufacturing a polarizing plate. If such an operation is performed, the above-mentioned cured layer can replace the above-mentioned protective film to achieve thinning. These curable resins can be used alone or in combination of two or more.
[0155] The polarizing film and polarizing plate obtained by using the polyvinyl alcohol-based film for manufacturing a polarizing film of the present embodiment have excellent polarizing properties and are preferably used in liquid crystal display devices such as mobile information terminals, personal computers, televisions, projectors, billboards, electronic calculators, electronic clocks, word processors, electronic papers, game machines, cameras, cameras, photo albums, thermometers, audio, automobiles, and instrument panels of machinery, as well as in sunglasses, anti-glare glasses, stereoscopic glasses, wearable displays, foldable displays, anti-reflection layers for display elements (CRT, LCD, organic EL, electronic paper, etc.), optical communication devices, medical devices, building materials, toys, etc.
[0156] Examples
[0157] Hereinafter, the present invention will be described more specifically with reference to examples. The present invention is not limited to the following examples as long as it does not exceed its gist.
[0158] It should be noted that "parts" and "%" in the examples refer to mass basis.
[0159] <Measurement conditions>
[0160] <GPC measurement>
[0161] A sample obtained by removing a plasticizer and a surfactant from 0.8 g of a polyvinyl alcohol-based film by rapid solvent extraction under the following conditions was used as a measurement sample, and a chromatogram was measured and obtained by gel permeation chromatography (GPC) under the following measurement conditions. Using a standard curve obtained from standard poly(ethylene oxide) and polyethylene glycol (PEO / PEG), the elution time at this time was converted to a molecular weight, and the weight-average molecular weight, molecular weight distribution (Mw / Mn), and molecular weight differential distribution curve of the polyvinyl alcohol-based film in terms of a standard sample (PEO / PEG) were obtained. In addition, the half-value width of the peak corresponding to polyvinyl alcohol was calculated from the molecular weight differential distribution curve.
[0162] [Conditions for rapid solvent extraction]
[0163] · Apparatus: Dionex ASE-20 (11 mL cell)
[0164] · Extraction solvent: methanol / water = 90 / 10
[0165] · Heating time: 5 minutes
[0166] Extraction pressure / standing time: 1500psi / 10 minutes
[0167] Flushing volume: 80%
[0168] Purge time: 60 seconds
[0169] Cycle: 2 cycles
[0170] Extraction times: 2 times
[0171] [GPC measurement conditions]
[0172] ·GPC equipment: Prominence manufactured by Shimadzu Corporation
[0173] Detector: RI, Shodex RI-501
[0174] Column: TSKgel α-M 13 μm 7.8 mm ID×30 cm manufactured by Tosoh Corporation was used.
[0175] Mobile phase: 0.2M NaNO 3 Aqueous solution
[0176] Mobile phase flow rate: 0.50mL / min
[0177] Column temperature: 35°C
[0178] Standard curve: 12 PEO / PEG standard samples with different molecular weights were used to create a standard curve.
[0179] <Weight Swelling Degree>
[0180] The polyvinyl alcohol film was cut into 100 mm × 100 mm and immersed in an ion exchange water tank adjusted to 30°C for 15 minutes. After immersion, the film was taken out and laid on the filter paper (5A). The filter paper (5A) was then overlapped on the film and a 150 mm × 150 mm × 4 mm (4.4 g / cm 2 ) on a SUS plate for 5 seconds to remove the attached water on the surface of the film. The film is quickly placed in a weighing bottle and the weight is measured, which is recorded as the weight of the film when swollen A. The above operation is carried out in an environment of 23°C and 50% RH. Then, the film is allowed to stand in a dryer at 160°C for 10 minutes and cooled in a dryer with drying material for 5 minutes to remove the moisture in the film. Thereafter, the film is taken out, quickly placed in a weighing bottle and the weight is measured, which is recorded as the weight of the film after drying B. Then, based on the weight of the film A when swollen and the weight of the film B after drying, the weight swelling degree is calculated using the following formula.
[0181] Weight swelling degree (%) = A / B × 100
[0182] <Dissolution amount in boric acid solution>
[0183] [Test method]
[0184] (i) Prepare 5 polyvinyl alcohol films with a width of 50 mm and a length of 100 mm, and install one of the films in a chuck portion with a size of 100 mm in width and 25 mm in length in a chuck stretching machine in a manner of a film width of 50 mm and a distance between chucks of 40 mm, (ii) immerse in a 30°C water bath for 2 minutes while stretching to a total stretching ratio of 2 times. Then, (iii) immerse in a 30°C aqueous solution containing 0.5 g / L iodine and 2.5 g / L potassium iodide for 20 seconds while stretching to a total stretching ratio of 3 times, and cut the polyvinyl alcohol film using the chuck portion to obtain a dyed polyvinyl alcohol film. (iv) Immerse the dyed polyvinyl alcohol film in 100 mL of a 60°C aqueous solution containing 44 g / L boric acid and 120 g / L potassium iodide for 5 minutes to obtain an eluate. (v) For the remaining 4 films, repeat the above steps (i) to (iv) in the same chemical solution used in each step, and use the solution of the above (iv) after repeating the above steps with 5 films (sometimes referred to as "boric acid solution") as the eluent for measurement.
[0185] (vi) After mixing 20 mL of the obtained measurement solution with 20 mL of a colorimetric reagent (a reagent containing 500 g of ion exchange water, 7.4 g of potassium iodide, 0.65 g of iodine, and 10.6 g of boric acid) at room temperature (23°C), the mixture was allowed to stand at 20°C for 15 minutes to prepare a sample solution. (vii) For the sample solution, the absorbance at a wavelength of 690 nm was measured using a spectrophotometer (UV-3600Plus manufactured by Shimadzu Corporation) and a quartz cell with an optical path length of 100 mm. (viii) Using a pre-prepared standard curve, the concentration (ppm) of the polyvinyl alcohol-based resin in the solution was calculated, and the total area of the film used for the elution was set to 50 mm × 40 mm × 5 sheets = 0.01 m 2 The concentration (ppm) of the obtained polyvinyl alcohol-based resin was converted into the amount of dissolution in the boric acid solution (ppm / m 2 ).
[0186] [evaluate]
[0187] 〇(Good): 120ppm / m 2 the following
[0188] ×(bad): more than 120ppm / m 2
[0189] [Creation of standard curve]
[0190] Ion exchange water was added to the polyvinyl alcohol resin so that the pure component of the polyvinyl alcohol resin became 200ppm, and the standard solution was obtained by heating and dissolving at 130°C for 1 hour using an autoclave. The standard solution was diluted with ion exchange water to obtain polyvinyl alcohol resin aqueous solutions with a concentration of 20ppm, 10ppm, 5ppm, 2ppm, 1ppm, 0.5ppm, 0.2ppm, and 0.1ppm. After 20mL of the aqueous solution of each concentration was mixed with 20mL of a colorimetric reagent (containing 500g of ion exchange water, 7.4g of potassium iodide, 0.65g of iodine, and 10.6g of boric acid) at room temperature, it was allowed to stand at 20°C for 15 minutes, and the absorbance at a wavelength of 690nm was measured using a spectrophotometer (UV-3600Plus manufactured by Shimadzu Corporation) and a quartz cell with an optical path length of 100mm. The polyvinyl alcohol resin concentration (ppm) was plotted against the absorbance at 690nm to prepare a standard curve.
[0191] <Amount dissolved in water>
[0192] [Test method]
[0193] The obtained polyvinyl alcohol film was adjusted to 23°C and 50% RH for 24 hours and then cut into 5 pieces of 100 mm x 100 mm (0.01 mm 2 ) test pieces were prepared, each of which was immersed in 1L of ion exchange water at 50°C for 1 minute and the operation was repeated for 5 pieces to obtain an eluate. After mixing 10mL of a colorimetric reagent (a reagent comprising 500g of ion exchange water, 7.4g of potassium iodide, 0.65g of iodine, and 10.6g of boric acid) with 10mL of the eluate at room temperature, the absorbance at a wavelength of 690nm was measured using a spectrophotometer (UV-3600Plus manufactured by Shimadzu Corporation), and the concentration (ppm) of the polyvinyl alcohol-based resin was calculated from a pre-prepared standard curve, and the amount of dissolution in water (ppm / m 2 ).
[0194] [evaluate]
[0195] ○ (good): dissolution amount is 900ppm / m 2 the following
[0196] × (bad): the elution amount is greater than 900 ppm / m 2
[0197] <Contamination of Chemical Solution>
[0198] [Test method]
[0199] The dissolution solution obtained in the dissolution amount test in the boric acid solution was left to stand at room temperature for 24 hours, and the presence or absence of precipitates was visually confirmed.
[0200] [evaluate]
[0201] ◎ (Excellent): No precipitate was visually confirmed
[0202] ○ (good): A small amount of precipitate was visually confirmed
[0203] × (bad): A large amount of precipitates was visually confirmed
[0204] <Elastic modulus>
[0205] A test piece of 120 mm in length and 15 mm in width was cut out from the obtained polyvinyl alcohol film, and the humidity was adjusted in a constant temperature and humidity chamber at 23°C and 40% RH for more than 24 hours. Then, a tensile test was performed along the length direction in an environment of 23°C and 40% RH using a "Precision Universal Testing Machine, Autograph (AG-IS)" manufactured by Shimadzu Corporation in accordance with JIS K7127:1999 (tensile speed 1000 mm / min, distance between chucks 50 mm) to obtain the elastic modulus (N / mm 2 ).
[0206] <Synthesis of Polyvinyl Alcohol Resin>
[0207] <Synthesis example 1>
[0208] 800 parts by mass of vinyl acetate and 0.32 parts by mass of cobalt (II) acetylacetonate were added to a reaction vessel equipped with a reflux condenser, a sample inlet, a nitrogen inlet, and a stirring blade, and nitrogen was bubbled for 30 minutes to replace the reaction vessel with nitrogen and expel the dissolved oxygen in the solution. Thereafter, the reaction vessel was immersed in a water bath and heated to 40°C, and 1.04 parts by mass of 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) was added as an initiator. Two hours after the addition of the initiator, the temperature was lowered, and the internal temperature was maintained at 30°C to start polymerization. It should be noted that the two hours after the addition of the initiator is an induction period in which polymerization does not proceed. Appropriate sampling was performed, and the progress of polymerization was confirmed by its solid content concentration. After the conversion rate of vinyl acetate reached 35%, 1.04 parts by mass of 1,1-stilbene was added as a polymerization terminator, and the mixture was stirred at 30°C for 30 minutes. It takes 7 hours from the addition of the initiator to the target conversion rate.
[0209] 30 minutes after the addition of the polymerization terminator, 4 parts by mass of acetic acid and 160 parts by mass of methanol were further added to the reaction vessel and the stirring was continued for 30 minutes. Purified water was added thereto to precipitate polyvinyl acetate, and the supernatant was removed, and the polyvinyl acetate was washed with water. After the obtained polyvinyl acetate was dissolved in methanol, methanol, vinyl acetate and water were distilled off under reduced pressure. After the viscosity increased, methanol was appropriately added to drive out the residual vinyl acetate to obtain a methanol solution of polyvinyl acetate.
[0210] The methanol solution of polyvinyl acetate obtained in this way is diluted with methanol until the concentration becomes 3.5% by mass, and is put into the same reaction container as above. The reaction container is immersed in a water bath and heated in a manner that the internal temperature becomes 50°C. 120 parts by mass of a methanol solution of 3.6% by mass of sodium hydroxide are added thereto to start the saponification reaction. If the saponification reaction proceeds, saponified products will precipitate, but stirring is continued while maintaining this state. The saponified product obtained 2 hours after the addition of the methanol solution of sodium hydroxide is filtered, put into the reaction container again, 500 parts by mass of methanol is added thereto and heated to 50°C. The saponification reaction is promoted by adding 180 parts by mass of a methanol solution of 3.6% by mass of sodium hydroxide thereto and reacting it for 3 hours. Thereafter, 4.2 parts by mass of acetic acid are added for neutralization, and the saponified product is obtained while washing with methanol and filtering. For the obtained saponified product of 100 parts by mass, 500 parts by mass of methanol are added twice, washed at 50°C for 30 minutes and filtered. The washed saponified product was dried in a vacuum dryer at 50°C for 12 hours to obtain a polyvinyl alcohol resin (1) (weight average molecular weight 73400; saponification degree 99.8 mol %; Mw / Mn=2.07; half value width of molecular weight differential curve 0.70).
[0211] <Synthesis example 2>
[0212] 650 parts by mass of vinyl acetate and 131 parts by mass of methanol were added to a reaction vessel equipped with a reflux condenser, a sample inlet, and a stirring blade, and the reaction vessel was immersed in a water bath and heated. After observing the reflux from the condenser (internal temperature was about 60°C), 0.052 parts by mass of 2,2'-azobis(isobutyronitrile) was added as an initiator. During the polymerization, the temperature of the water bath was appropriately adjusted to continue the reflux from the condenser and sampling was performed. The progress of the polymerization was confirmed by its solid content concentration. After the conversion rate of vinyl acetate reached 50%, 0.013 parts by mass of m-dinitrobenzene and 500 parts by mass of methanol were added as polymerization terminators to terminate the polymerization. It took 5 hours from the addition of the initiator until the target conversion rate was reached.
[0213] Methanol and vinyl acetate in the obtained solution after polymerization were distilled off under reduced pressure. After the viscosity increased, methanol was appropriately added to drive out the remaining vinyl acetate to obtain a methanol solution of polyvinyl acetate.
[0214] The subsequent synthesis steps were carried out in the same manner as in Synthesis Example 1 to obtain a polyvinyl alcohol-based resin (2) (weight average molecular weight: 79,000; saponification degree: 99.8 mol %; Mw / Mn=2.27; half value width of the molecular weight differential curve: 0.95).
[0215] <Synthesis example 3>
[0216] 650 parts by mass of vinyl acetate and 85 parts by mass of methanol were added to a reaction container equipped with a reflux condenser, a sample inlet, and a stirring blade, and the reaction container was immersed in a water bath and heated. After the reflux from the condenser was observed (the internal temperature was about 60°C), 0.13 parts by mass of 2,2'-azobis(isobutyronitrile) was added as an initiator. During the polymerization, the temperature of the water bath was appropriately adjusted to continue the reflux from the condenser and samples were taken. The progress of the polymerization was confirmed by the solid content concentration. After the conversion rate of vinyl acetate reached 70%, 0.033 parts by mass of m-dinitrobenzene and 500 parts by mass of methanol were added as polymerization terminators to terminate the polymerization. It took 3.5 hours from the addition of the initiator until the target conversion rate was reached.
[0217] The subsequent synthesis steps were carried out in the same manner as in Synthesis Example 1 to obtain a polyvinyl alcohol-based resin (3) (weight average molecular weight: 79,700; saponification degree: 99.8 mol %; Mw / Mn=2.36; half value width of the molecular weight differential curve: 0.97).
[0218] <Synthesis example 4>
[0219] 650 parts by mass of vinyl acetate and 65 parts by mass of methanol were added to a reaction container equipped with a reflux condenser, a sample inlet, and a stirring blade, and the reaction container was immersed in a water bath and heated. After the reflux from the condenser was observed (the internal temperature was about 60°C), 0.0325 parts by mass of 2,2'-azobis(isobutyronitrile) was added as an initiator. During the polymerization, the temperature of the water bath was appropriately adjusted to continue the reflux from the condenser and samples were taken. The progress of the polymerization was confirmed by the solid content concentration. After the conversion rate of vinyl acetate reached 50%, 0.01 parts by mass of m-dinitrobenzene and 500 parts by mass of methanol were added as polymerization terminators to terminate the polymerization. It took 5 hours from the addition of the initiator until the target conversion rate was reached.
[0220] The subsequent synthesis steps were carried out in the same manner as in Synthesis Example 2 to obtain a polyvinyl alcohol-based resin (4) (weight average molecular weight 101,000; saponification degree 99.8 mol %; Mw / Mn=2.42; half value width of the molecular weight differential curve 0.92).
[0221] (Example 1)
[0222] <Production of polyvinyl alcohol film]
[0223] A composition was obtained by adding 12 parts by mass of glycerin as a plasticizer and 0.1 parts by mass of polyoxylaurylamine as a surfactant to 100 parts by mass of the polyvinyl alcohol-based resin (1) obtained in the above synthesis example, and ion exchange water was added to the composition so that the concentration of the composition became 19% by mass. The mixture was heated and dissolved at 130° C. for 1 hour using an autoclave to obtain a polyvinyl alcohol-based resin aqueous solution.
[0224] The polyvinyl alcohol resin aqueous solution was continuously cast onto a polyethylene terephthalate (PET) film (film thickness 125 μm) as a substrate film in such a manner that the film thickness after drying was 45 μm, and dried for 7 minutes in a drying furnace heated to 110° C. Thereafter, the polyvinyl alcohol film that had undergone the drying process was peeled off from the substrate film, and heat-treated for 1 minute in a drying furnace at 120° C. to obtain a polyvinyl alcohol film.
[0225] Table 1 shows the properties of the obtained polyvinyl alcohol-based film.
[0226] (Example 2)
[0227] The polyvinyl alcohol film having undergone the drying step was peeled off from the base film and then a polyvinyl alcohol film was obtained in the same manner as in Example 1 except that the heat treatment temperature in the drying furnace was changed to 130° C. The properties of the obtained polyvinyl alcohol film are shown in Table 1.
[0228] (Comparative Example 1)
[0229] A composition was obtained by adding 12 parts by mass of glycerin as a plasticizer and 0.1 parts by mass of polyoxylaurylamine as a surfactant to 100 parts by mass of the polyvinyl alcohol-based resin (2) obtained in the above synthesis example, and ion exchange water was added to the composition so that the concentration of the composition became 19% by mass. The mixture was heated and dissolved at 130° C. for 1 hour using an autoclave to obtain a polyvinyl alcohol-based resin aqueous solution.
[0230] The polyvinyl alcohol resin aqueous solution was cast onto a polyethylene terephthalate (PET) film (125 μm) as a substrate film so that the film thickness after drying was 45 μm, and dried for 7 minutes in a drying furnace heated to 110° C. Thereafter, the polyvinyl alcohol film that had undergone the drying step was peeled off from the substrate film to obtain a polyvinyl alcohol film.
[0231] Table 1 shows the properties of the obtained polyvinyl alcohol-based film.
[0232] (Comparative Example 2)
[0233] A polyvinyl alcohol film was obtained by the same procedure as in Comparative Example 1 except that the polyvinyl alcohol resin (3) obtained in the above-mentioned Synthesis Example was used, the polyvinyl alcohol film after the drying step was peeled off from the base film, and then heat-treated in a drying furnace heated to 130° C. for 1 minute. The properties of the obtained polyvinyl alcohol film are shown in Table 1.
[0234] (Comparative Example 3)
[0235] A composition was obtained by adding 12 parts by mass of glycerin as a plasticizer and 0.1 parts by mass of polyoxylaurylamine as a surfactant to 100 parts by mass of the polyvinyl alcohol-based resin (4) obtained in the above synthesis example, and ion exchange water was added to the composition so that the concentration of the composition became 19% by mass. The mixture was heated and dissolved at 130° C. for 1 hour using an autoclave to obtain a polyvinyl alcohol-based resin aqueous solution.
[0236] The polyvinyl alcohol resin aqueous solution was cast onto a polyethylene terephthalate (PET) film (125 μm) as a substrate film so that the film thickness after drying was 45 μm, and dried for 7 minutes in a drying furnace heated to 110° C. Thereafter, the polyvinyl alcohol film that had undergone the drying process was peeled off from the substrate film to obtain a polyvinyl alcohol film. The properties of the obtained polyvinyl alcohol film are shown in Table 1.
[0237] (Comparative Example 4)
[0238] The same procedure as in Comparative Example 3 was followed except that the dried polyvinyl alcohol film was peeled off from the base film and then heat treated in a drying furnace heated to 130° C. for 1 minute to obtain a polyvinyl alcohol film.
[0239] (Comparative Example 5)
[0240] A composition was obtained by mixing 12 parts by mass of glycerol as a plasticizer and 0.1 parts by mass of polyoxylaurylamine as a surfactant with respect to 100 parts by mass of the polyvinyl alcohol resin (4) obtained by the above synthesis example, and ion exchange water was added to the composition so that the concentration of the composition became 29% by mass. The mixture was heated to 140°C and dissolved under pressure while stirring to obtain a uniformly dissolved polyvinyl alcohol resin aqueous solution. The polyvinyl alcohol resin aqueous solution was then supplied to a twin-screw extruder having a discharge port and degassed. The aqueous solution temperature was set to 95°C, and the film was ejected and cast from a T-slit die outlet onto a rotating casting drum (ejection speed 2.5 m / min, surface temperature 88°C) for film formation. The film was peeled off from the casting drum, and the surface and back of the film (contact surface with the casting drum) were alternately contacted with a total of 15 hot rollers in a temperature range of 75°C to 100°C while being dried. Then, a floating dryer was used to blow hot air at 125°C from both sides of the film for heat treatment. Finally, the two ends were slit and the film was rolled up to obtain a polyvinyl alcohol film having a thickness of 45 μm, a width of 5 m, and a length of 5 km. The properties of the obtained polyvinyl alcohol film are shown in Table 1.
[0241] [Table 1]
[0242]
[0243] For the polyvinyl alcohol films of Examples 1 and 2, the half-value width of the peak corresponding to polyvinyl alcohol in the molecular weight differential distribution curve of gel permeation chromatography is within the range defined in claim 1. Therefore, a polyvinyl alcohol film for polarizing film manufacturing is obtained in which the amount of polyvinyl alcohol resin dissolved in a boric acid-containing solution during polarizing film manufacturing is small, and contamination of the solution tank during polarizing film manufacturing is suppressed, thereby enabling a polarizing film with few foreign matter defects to be obtained with good productivity.
[0244] In contrast, it can be seen that for the polyvinyl alcohol films of Comparative Examples 1 to 5, the half-value width of the peak corresponding to polyvinyl alcohol in the molecular weight differential distribution curve of gel permeation chromatography is outside the range defined in claim 1. Therefore, the amount of polyvinyl alcohol resin eluted into the boric acid-containing solution during the manufacture of the polarizing plate is large, and it is easy to contaminate the solution tank during the manufacture of the polarizing film.
[0245] It should be noted that the polarizing film obtained by using the polyvinyl alcohol-based film of the example is a polarizing film having no foreign matter defects and excellent polarizing performance.
[0246] In the above-mentioned embodiment, although the specific form in this invention is shown, the above-mentioned embodiment is a mere example, and is not to be interpreted as limiting. Various modifications which are obvious to a person skilled in the art are intended to be included in the scope of this invention.
[0247] Industrial Applicability
[0248] The polyvinyl alcohol-based film for polarizing film manufacturing of the present invention is preferably used for mobile information terminals, personal computers, televisions, projectors, billboards, electronic calculators, electronic clocks, word processors, electronic paper, game consoles, video cameras, cameras, photo albums, thermometers, audio equipment, automobiles, liquid crystal display devices of mechanical instruments, sunglasses, anti-glare glasses, stereo glasses, wearable displays, foldable displays, rollable televisions, rollable displays, anti-reflection films for display elements (CRT, LCD, organic EL, electronic paper, etc.), optical communication equipment, medical equipment, building materials, toys, etc. to manufacture polarizing film blanks.
Claims
1. A polyvinyl alcohol film for producing a polarizing film, characterized in that: The half-value width of the peak corresponding to polyvinyl alcohol in the molecular weight differential distribution curve of gel permeation chromatography is less than 0.9, and the dissolution amount in the dissolution test in boric acid solution under the following condition A is 120 ppm / m 2 the following, Condition A: (i) Five polyvinyl alcohol films with a width of 50 mm were prepared, and one of the films was mounted on a chuck stretching machine with a chuck distance of 40 mm. (ii) Stretching to 2 times while immersing in a 30°C water bath for 2 minutes, (iii) stretching to 3 times while immersing in an iodine / potassium iodide aqueous solution at 30° C. for 20 seconds, (iv) Immerse in 100 mL of a 60°C boric acid / potassium iodide aqueous solution for 5 minutes, (v) Repeating the steps (i) to (iv) in the same aqueous solution used in each step for each of the remaining 4 films, and using the solution of (iv) after repeating the steps for 5 films as the eluent, (vi) 20 mL of the eluate was mixed with 20 mL of a color developing reagent containing boric acid / iodine / potassium iodide and the mixture was allowed to stand at 20° C. to prepare a sample solution, (vii) For the sample solution, a quartz cell with an optical path length of 100 mm was used to obtain a UV-vis spectrum, and the absorbance at 690 nm was read. (viii) The concentration of the polyvinyl alcohol resin in the elution solution was calculated using a calibration curve of polyvinyl alcohol resin concentration versus absorbance at 690 nm prepared using solutions with known polyvinyl alcohol resin concentrations, and corrected using the area of the polyvinyl alcohol film used for elution.
2. The polyvinyl alcohol-based film for producing a polarizing film according to claim 1, characterized in that: The thickness is 10 to 50 μm.
3. The polyvinyl alcohol-based film for producing a polarizing film according to claim 1 or 2, characterized in that: The weight swelling degree is 185-200%.
4. A method for producing a polyvinyl alcohol-based film for producing a polarizing film according to claim 1 or 2, characterized in that: The method comprises: a film forming step of continuously ejecting and casting an aqueous solution of a polyvinyl alcohol-based resin onto a casting die or a belt to form a film to obtain a film, a drying step of drying the film obtained by the film forming at 105° C. or above, and a heat treatment step of heat treating the dried film.
5. A polarizing film, characterized in that: It is obtained by using the polyvinyl alcohol-based film for producing a polarizing film according to claim 1 or 2.
Citation Information
Patent Citations
Vinyl alcohol-based polymer film
JP2009221462A
Polyvinyl alcohol removal device and method of manufacturing polarizer
JP2021047397A